PENGARUH PENERAPAN LKS BERBASIS MODEL PEMBELAJARAN KREATIF PRODUKTIF TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMAN 1 RANAH BATAHAN - Alfi Sahrin; Amali Putra; Fatni Mufit (Universitas Negeri Padang, 2015)
Student’s low physics learning outcomes is predicted as the result of less effective and creative learning strategies used in the learning process. One of the strategies for effective and creative learning is a creative and productive based student worksheet learning model. This study aims to determine the effect of the application of creative and productive based student worksheet learning model towards productive physics learning outcomes in class X SMA N 1 Ranah Batahan. This type of research is a quasi-experimental research (Quasi Experiment Research) with the study design Randomized Control Group Only Design. The study population was all class X students enrolled in the academic year 2013/2014. Sampling was done by cluster random sampling technique. Research data collection techniques such as written tests for cognitive, and scoring rubrics for psychomotor aspects. Data were analyzed using t-test at the 0.05 significance level. The result obtained by the average value of the experimental class in the cognitive is 70.5 and the control class is 62.58, on the psychomotor obtained average value is 77.13 and the experimental control class is 72.96. The hypothesis was tested using the t-test, the cognitive domain obtained t = 2.51, the affective domain obtained t = 7.69, on the psychomotor obtained t = 4.27, and the table = 1.67 significance level of 0.05, meaning t count>t table so that Ho is rejected. The conclusion from this study is that there is a significant impact of the usage of creative and productive based student worksheet learning model towards the results of physics learning in class X SMA N 1 Ranah Batahan